2022
DOI: 10.1007/s12178-022-09783-2
|View full text |Cite
|
Sign up to set email alerts
|

Malunion of Pediatric Forearm Shaft Fractures: Management Principles and Techniques

Abstract: Purpose of Review Clinically significant malunion of forearm diaphyseal fractures is an uncommon but potentially disabling condition amongst children and adolescents. We present the preoperative evaluation, including imaging, and discuss surgical indications and contemporary approaches to manage such patients, including an illustrative case. Recent Findings While advances in three-dimensional (3D) simulation, modeling, and patient-specific instrumentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The conventional approach for acute correction of post-traumatic malunion deformities in children is represented by a corrective osteotomy at the deformity site (mainly closing-wedge osteotomy, opening-wedge osteotomy, or oblique osteotomy) planned on plain radiographs, with or without an additional osteotomy of the other bone, to achieve acceptable ulnar variance and satisfactory prono-supination [ 1 , 2 , 15 , 16 , 17 , 18 , 19 , 20 ]. Since the spread of computer-aided planning and the introduction of PSIs in the last two decades, many different options have become viable to improve surgical accuracy and final outcome [ 1 , 4 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional approach for acute correction of post-traumatic malunion deformities in children is represented by a corrective osteotomy at the deformity site (mainly closing-wedge osteotomy, opening-wedge osteotomy, or oblique osteotomy) planned on plain radiographs, with or without an additional osteotomy of the other bone, to achieve acceptable ulnar variance and satisfactory prono-supination [ 1 , 2 , 15 , 16 , 17 , 18 , 19 , 20 ]. Since the spread of computer-aided planning and the introduction of PSIs in the last two decades, many different options have become viable to improve surgical accuracy and final outcome [ 1 , 4 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, acute correction of post-traumatic forearm deformities in children is generally achieved with a closing-wedge osteotomy, an opening-wedge osteotomy, or an oblique osteotomy of one or both bones [ 1 , 2 ]. The precision of these techniques has significantly improved since the introduction of virtual surgical planning (VSP) and the spread of 3D-printed patient-specific instruments (PSIs) in orthopedic surgery [ 1 , 2 , 3 , 4 ]. Many authors have published methods and algorithms to precisely align a malunited bone to the shape of the uninjured contralateral with a single oblique cut [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering cadaveric studies, it has been shown that malunion of less than 10° causes minimal pronation and supination limitation, while higher degrees cause significant loss in the same movements [4,5,7]. Surgical treatment is recommended to prevent functional and cosmetic problems [8][9][10].…”
Section: Discussionmentioning
confidence: 99%